2011
DOI: 10.1007/s00203-011-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the surface proteins of Acidithiobacillus ferrooxidans strain SP5/1 and the new, pyrite-oxidizing Acidithiobacillus isolate HV2/2, and their possible involvement in pyrite oxidation

Abstract: Two strains of rod-shaped, pyrite-oxidizing acidithiobacilli, their cell envelope structure and their interaction with pyrite were investigated in this study. Cells of both strains, Acidithiobacillus ferrooxidans strain SP5/1 and the moderately thermophilic Acidithiobacillus sp. strain HV2/2, were similar in size, with slight variations in length and diameter. Two kinds of cell appendages were observed: flagella and pili. Besides a typical Gram-negative cell architecture with inner and outer membrane, enclosin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 78 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…Up to now, p3-symmetry was thought to be unique to the order Sulfolobales , given that all investigated species from this group had this symmetry and a consistent lattice value (Baumeister & Lembcke, 1992; Deatherage et al , 1983; Grogan, 1996; Klingl et al , 2013; König et al , 2007; Lembcke et al , 1991, 1993; Prüschenk & Baumeister, 1987; Prüschenk et al , 1987; Taylor et al , 1982; Veith et al , 2009). Thus, the occurrence of p3-symmetry in the thaumarchaeote EN76 T excludes this characteristic as a taxonomic marker for the order Sulfolobales (Klingl et al , 2011; König et al , 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Up to now, p3-symmetry was thought to be unique to the order Sulfolobales , given that all investigated species from this group had this symmetry and a consistent lattice value (Baumeister & Lembcke, 1992; Deatherage et al , 1983; Grogan, 1996; Klingl et al , 2013; König et al , 2007; Lembcke et al , 1991, 1993; Prüschenk & Baumeister, 1987; Prüschenk et al , 1987; Taylor et al , 1982; Veith et al , 2009). Thus, the occurrence of p3-symmetry in the thaumarchaeote EN76 T excludes this characteristic as a taxonomic marker for the order Sulfolobales (Klingl et al , 2011; König et al , 2007). …”
Section: Resultsmentioning
confidence: 99%
“…The intense signal in the PAS staining indicated that the Kustd1514 protein is highly glycosylated, which is a common feature of several S-layer proteins (49). In bacteria, O-glycosylation seems most abundant, although some N-glycosylated (S-layer) proteins have also been described (28,58). The Kustd1514 protein contains both potential O-and N-glycosylation sites, as found by a manual search of the protein sequence for strict "consensus" sequences and by using the GlycoPP prediction server (59).…”
Section: Discussionmentioning
confidence: 99%
“…Kuenenia stuttgartiensis" cells is thus invested in synthesizing S-layer proteins, and it is therefore obvious to raise the question of which function the Slayer has for this anammox bacterium. Multiple functions for Slayers in prokaryotes have been proposed (65), including protection against predation (68,69), adhesion of cell-associated exoenzymes (70), osmoprotection (71), and maintaining cell shape and integrity (58,64). The latter function seems especially interesting in the case of anammox bacteria, since they are proposed to lack peptidoglycan and might therefore be in need of a structure that maintains cell shape and integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After blotting on a filter paper, the samples were washed twice on a drop of double distilled water and blotted each time. Finally, the proteins were negatively stained with 2% (w/v) uranyl acetate for 20 s, blotted again on filter paper and left for air drying (52,53). Electron microscopy and further analysis was carried out on a JEOL JEM-2100 transmission electron microscope (JEOL, Tokyo, Japan) operated at 120 kV.…”
Section: Methodsmentioning
confidence: 99%